MODELING OF TRANSIENT FLOW FOR THE ESTIMATION OF RESERVOIR PRESSURE - YEE, HON VAl (2010)
The lack of reservoir pressure data has always posed a problem in production planning and oil recovery optimization. Subsurface reservoir pressure data acquisition through intrusive well intervention method might lead to loss of production, increased risk, inconvenience and logistical problems and might involve additional expense and time. An alternative to well intervention is to employ transient flow modeling to estimate the reservoir pressure. Transient flow modeling technique is a proven tool which has been applied for years by facilities engineers for pipeline and slug-catcher design. However, transient flow modeling for estimating reservoir pressure requires further investigation to evaluate its applicability in well bore condition. In this research, a transient flow modeling technique was developed to estimate the reservoir pressure upon well shut-in. A mathematical workflow for the transient flow model was devised to simulate the hydrocarbon fluid redistribution in a well, from steady state flow until the fluid columns were fully segregated upon equilibrium over the shut-in period. The salient features of this transient flow modeling technique were described, including simulation of reservoir fluid influx, wellhead gas chamber volume, gas-liquid interface movement, wellhead and bottom-hole pressure build-up over the fluid redistribution period during well shut-in. Three producing oil wells from different reservoirs 111 Malay Basin were selected to assess the transient flow modeling capability. The evaluation showed that the estimated wellhead and bottom-hole build-up pressure were in good agreement with the pressure build-up survey results obtained from the field. This verified that the developed transient flow modeling could closely simulate the fluid redistribution of a shut-in well and estimate a reliable reservoir pressure.